Thrombocytopenia as a Clinical Biomarker of Retinopathy of Prematurity - Sutyawan, I Wayan Eka; Surasmiati, Ni Made Ayu; Agrasidi, Putu Anindya; Dwianggita, Priscilla; Anggara, Stephanus Anggara (Folia Medica Indonesiana, 2023)
Highlights: • This is the first systematic review investigating thrombocytopenia and its association with retinopathy of prematurity. • Thrombocytopenia can be a useful clinical biomarker in retinopathy of prematurity screening, considering the quick, affordable, and widespread availability of the examination. Abstract Retinopathy of prematurity (ROP) is the primary cause of childhood blindness. It arises from the underdevelopment of retinal blood vessels in premature infants. Platelets have a vital function in the regulation of angiogenesis. Thus, thrombocytopenia may contribute to the progression of ROP. The objective of this systematic study was to examine the relationship between thrombocytopenia and ROP. The PubMed and Cochrane Library databases were accessed to search for retrospective, case-control, and cross-sectional studies. This study adhered to the guidelines outlined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The literature search resulted in nine records to be analyzed in our review. All the selected studies were conducted between 2017 and 2022. Seven studies reported that the prevalence of thrombocytopenia in infants with ROP ranged from 18.37% to 71%. The frequency of thrombocytopenia in preterm children without ROP was between 5.71% and 21%. Thrombocytopenia was identified as a risk factor for ROP in seven studies, with the odds ratio (OR) for thrombocytopenia ranging from 2.8 to 6.69. Thrombocytopenia in premature infants can potentially serve as a clinical biomarker in the screening of type 1 ROP. This finding suggests that thrombocytopenia may contribute to the pathophysiology of ROP. Further research is necessary to determine the critical threshold platelet count for thrombocytopenia in infants with ROP.